In Vitro Antimicrobial Effects of 3 Root Canal Sealers on Actinomyces Radicidentis - Barbero-Navarro, Ignacio; Galera-Ruiz, Hugo; Pereira, Mario; Guerreiro, Diogo; Machuca-Portillo, María del Carmen; López del Valle, Lydia (Puerto Rico Health Sciences Journal, 2014)
Objective: To determine the in vitro antimicrobial effects of 3 endodontic sealers— AH Plus®, Sealapex®, and Tubli-Seal®—on Actinomyces radicidentis, a bacterial species commonly found in root canals. Methods: Prior to the experimental procedures, bacterial identification tests, such as Gram staining, catalase, and API 20A, were performed, and the bacteria were identified as A. radicidentis. The agar diffusion susceptibility test was performed to determine the areas of bacterial growth inhibition and, consequently, the microbial resistance of the 3 sealers against A. radicidentis. Chlorhexidine was used as a positive control, and saline solution was used as a negative control. Results: Tubli-Seal cement had an average diameter of inhibition zones in the 3 panels of 22.73 mm, that of AH Plus was 17.13 mm, and that of Sealapex, 11.99 mm. A one-way ANOVA test showed that there were significant differences between the 3 cements (p<0.05). Conclusion: Tubli-Seal® showed the highest levels of antimicrobial activity, which was followed by AH Plus® with the next highest levels and, finally, Sealapex® with the lowest levels of antimicrobial activity.